Handbook of Literary Criticism and Ethics - Ganteau, Jean-Michel; Onega, Susana (Handbooks of Literary and Cultural Studies, 2026)
Storytelling has always occupied a central role in the configuration of self and world. However, the patterns of meaning it creates are often controversial, as they are metaphoric or holistic. The Handbook of Literary Criticism and Ethics provides a clear roadmap to understanding the changing ethical value attributed to Western literature from the ancient Greeks to the present. Readers will gain a nuanced apprehension of the evolution of literary forms, both alongside and against the dominant cultural paradigms. What ensues are critical reconfigurations of ethics and aesthetics.